The Influence of Budget Preparation Participation and Work Motivation on Employee Performance (Study at the West Java Regional Police Mobile Brigade Corps) - Riska Fitriyani; Gun Gunawan Rachman; Dedy Sudarmadi (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of budgetary participation and work motivation on employee performance at the West Java Regional Police Mobile Brigade Unit. The approach used was quantitative with an explanatory survey method to test the causal relationship between variables. Data were obtained through an ordinal scale questionnaire distributed to 33 respondents selected using a purposive sampling technique from a population of 80 employees. The research variables consisted of budgetary participation, work motivation, and employee performance, each measured through indicators that have been systematically operationalized. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) to test the measurement model and structural model simultaneously. The results showed that budgetary participation had a positive and significant effect on employee performance, and work motivation had a positive and significant effect on employee performance. Both variables were categorized as good based on descriptive analysis, although there were still several aspects that needed to be improved, especially in terms of involvement and achievement motivation. These findings indicate that increasing participation and work motivation can encourage more optimal employee performance. This research is expected to contribute to the development of human resource management and management accounting science and become a reference for improving employee performance in public organizations.